2022
DOI: 10.18178/ijiet.2022.12.9.1709
|View full text |Cite
|
Sign up to set email alerts
|

Teacher's Perspective on the Effectiveness of Online Learning during the COVID-19 Pandemic

Abstract: Online learning research has garnered widespread interest during the COVID-19 pandemic. However, the perspective of elementary and secondary school teachers on online learning is largely unknown. As such, this study sought to ascertain the perspectives of 276 elementary and secondary school teachers on online learning during the COVID-19 pandemic in Indonesia. This study adopted a survey method using an online questionnaire to collect data, which was distributed via Google Forms. A descriptive analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Furthermore, some students are not yet skilled in using applications/technology. In line with the findings of Albet et al [36], they found that teachers believed online learning was ineffective during the COVID-19 pandemic. One of the reasons for this conclusion was their inability to adapt to the new culture of online teaching, which could be a result of their classes not being prepared for online instruction.…”
Section: Ict-supported Calculus Learning Concept Designsupporting
confidence: 82%
“…Furthermore, some students are not yet skilled in using applications/technology. In line with the findings of Albet et al [36], they found that teachers believed online learning was ineffective during the COVID-19 pandemic. One of the reasons for this conclusion was their inability to adapt to the new culture of online teaching, which could be a result of their classes not being prepared for online instruction.…”
Section: Ict-supported Calculus Learning Concept Designsupporting
confidence: 82%
“…Unfortunately, there are no perfect evaluation systems at present. Since the current research on online teaching is mostly limited to a certain subject [8,9], or the evaluation of learning effect is also based on some certain platform [10,11], no matter from the perspective of students or teachers [12,13], while the evaluation of the advantages and disadvantages of various platforms and the horizontal learning effect are rare. This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Thematic learning itself is an education system that allows students, individually and in groups, to actively seek, explore, and discover scientific concepts and principles in a holistic, meaningful, and authentic" way (Kadir & Asrohah, 2015). "Thematic learning is integrated learning that prioritizes student participation in learning, involves students actively in the learning process, and creates problem-solving situations based on student needs (Nurmawati & Yulisetiani, 2022). Thematic learning allows students to learn and play with high creativity.…”
Section: Introductionmentioning
confidence: 99%